A comprehensive guide to greenwashing phenomena, contexts, and trends : the mean, lean washing machine - Lucia Gatti; Ludovico Conti; Peter Seele (A comprehensive guide to greenwashing phenomena, contexts, and trends : the mean, lean washing machine, 2025)
"Green communication can improve a firm's reputation and performance, regardless of their genuine green conduct. This book investigates the greenwashing phenomenon and maps how firms mislead consumers by not delivering on their environmental promises. The book provides a comprehensive list of 39 different aspects of 'washing', covering significant topics such as bluewashing, ethicswashing, poorwashing, pinkwashing, wokewashing and blockchainwashing. Chapters uniquely combine a business perspective with a more philosophical outlook, considering the wider implications of organisations not fulfilling important ethical promises, like societal polarisation and change of corporate scope. New concepts like greenlash, greenwashing truthers and greenhushing provide a bigger-picture perspective on this divisive corporate practice. Academics focusing on management and marketing, particularly green marketing and corporate social responsibility, will find this book to be an insightful read. It is also invaluable to practitioners in corporate communications, and will help policymakers in understanding current washing practices"–
10.4337/9781035328246; 10.4337/9781035328246